Evaluation of resistance to Tomato severe rugose virus (ToSRV) in Capsicum spp. genotypes - Rocha, Kelly C. G. [UNESP]; Marubayashi, Julio M. [UNESP]; Mituti, Tatiana [UNESP]; Gioria, Ricardo; Kobori, Rômulo F.; Melo, Arlete M. T.; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Sociedade Brasileira de Fitopatologia, 2012)
Tomato severe rugose virus (ToSRV) is the predominant species of begomovirus in São Paulo State, Brazil, and infects primarily tomato and pepper plants. There is no information about genetic resistance of pepper to this virus, so in this work the reaction of 29 genotypes of Capsicum spp. was evaluated by inoculation of two ToSRV isolates: ToSRV-Sk (isolated from a tomato plant) and ToSRV-PJU (isolated from a pepper plant). For both isolates, two C. annuun genotypes (Catarino Cascabel - México and Silver) showed no symptoms 30 days after inoculation (d.a.i). In a second experiment, these two genotypes were evaluated for 150 d.a.i and, again, no symptoms could be observed. However, the virus was detected by RCA-PCR, indicating that both genotypes are susceptible, but less affected by ToSRV infection. Catarino Cascabel - México and Silver can be indicated for use in breeding programs for resistance of pepper to ToSRV.
Keywords: Bemisia tabaci; chili peper; geminivirus; tolerance; sweet pepper